Traffic Infrastructure as an Impulsive Factor for Development of Tourism in Kosovo - RAMADANI, Ibrahim; ÇELA, Tomor (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).05, 2019)
Traffic and tourism are two most important branches of the economy, representing a synonym for each other. The word tourism itself means traffic or traveling, hence traffic and tourism are closely related. Through traffic many areas, being them touristicaly receptive or emitive, are connected, resulting in functioning of the demand-offer occurrence. The level of traffic development therefore determines the level of touristic movement onto certain region. Construction of the roads and extention of its network enables tourists to be closer to touristic motifs and, on the other hand investors are being offered the opportunity for building receptive capacities. Extension of the road network in Kosovo, as well as in majority of the world countries, is conditioned by physico-geographic and socio-economic factors. According to the world classification for road network density of 1000 km² lists Kosovo within a group of countries with an average stage of road development, along with some countries from the Southern Europe. This level of traffic organization is automatically being reflected into the development of tourism. This study aims to evaluate the development level of the road network and the tourism potential offered by Kosovo; components that correlate with each other, as the development of tourism depends from the level of traffic development. In addition to the expansion and modernization of the road network, many natural and anthropogenic values are turning into important touristic sights as well. Hence, traffic in many world countries, as well as in Kosovo is reflecting positively into development of tourism as an important economic branch.